1989
DOI: 10.3109/02699058909004553
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent control in the treatment of brain-injured clients

Abstract: Three brain-injured clients failed to respond significantly to consequence management programmes designed to increase attendance, use of a cane, and to reduce unauthorized breaks. When antecedent stimulus control procedures were applied, attendance and use of a cane increased and unauthorized breaks decreased. The study shows that antecedent control may be the treatment of choice when treating brain-injured clients with memory loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…found that a contingent reward points system increased rehabilitation attendance in two adolescents; in one client this was enhanced with the addition of a response cost procedure. However, 100% attendance was only reached and sustained for both clients once financial rewards were introduced -in contrast to their Zencius, Wesolowski, Burke and McQuade (1989) study. Corrigan and colleagues (Corrigan et al, 2005;Corrigan & Bogner, 2007) conducted randomised controlled trials in adults with ABI receiving substance abuse treatment and found that financial incentives led to improved initial attendance at and engagement with treatment, which has been shown to be important in developing a therapeutic alliance and enhance subsequent retention (Newman, 1997), and reduced premature termination of treatment.…”
Section: Contingency Managementmentioning
confidence: 82%
See 4 more Smart Citations
“…found that a contingent reward points system increased rehabilitation attendance in two adolescents; in one client this was enhanced with the addition of a response cost procedure. However, 100% attendance was only reached and sustained for both clients once financial rewards were introduced -in contrast to their Zencius, Wesolowski, Burke and McQuade (1989) study. Corrigan and colleagues (Corrigan et al, 2005;Corrigan & Bogner, 2007) conducted randomised controlled trials in adults with ABI receiving substance abuse treatment and found that financial incentives led to improved initial attendance at and engagement with treatment, which has been shown to be important in developing a therapeutic alliance and enhance subsequent retention (Newman, 1997), and reduced premature termination of treatment.…”
Section: Contingency Managementmentioning
confidence: 82%
“…In 4 of their studies, contracting alone increased adherence to rehabilitation but this behaviour change was not sustained without additional intervention. In another study, a verbal contract combined with a contingent financial reward was ineffective in increasing use of a walking cane (Zencius, Wesolowski, Burke & McQuade, 1989).…”
Section: Consequence Management Behavioural Contractingmentioning
confidence: 98%
See 3 more Smart Citations